Orthographic Analysis of Social Media Discourse: The Case of WhatsApp Messages of Undergraduate Students at the National University of Lesotho - Kolobe, Maboleba; Ekanjume, Beatrice (Journal of Language and Literature, 2023)
This paper examined the orthography of words used by the National University of Lesotho undergraduate students on WhatsApp. Although language is regarded as a coherent and homogeneous system, it can also be studied in its variations across time and space and how it is actually used in social interaction. Youth immersion in the use of social media has successfully made the presence of the digital era to be felt not only in social life but also in communicative competencies. This paper recognised the youth linguistic creativity as a concept that characterised nomenclature of spelling conventions observed on social media. Using voluntary participatory approach, data was collected from undergraduate students majoring in English at the University who volunteered to share their WhatsApp posts for the purpose of this study. Data revealed that youths’ social media discourse featured different orthographic representations as a result of accent stylisation, substitution, acronym, hybrid, clipping, coalescence, onomatopoeic spellings and deletions. The paper concluded that youth social media discourse deviates from conventional spellings, and thus serves as a linguistic innovation from the part of the youths. It further concluded that social media discourse is a true reflection of language diversity in this digital era especially with regards to the language of the youth globally.